The enhanced role of canals and route choice due to disruptions in maritime operations - Zis, Thalis (My University, 2023)
Purpose – This paper focusses on the aftermath of disruptions and the importance of the two largest canals (Suez and Panama), commenting on how during the pandemic the canal fees were lowered. Considering the ongoing efforts to decarbonize shipping, some of the ongoing disruptions will help reach these objectives faster. Design/methodology/approach – Following a literature review of route choice in shipping, and a presentation of significant disruptions in recent years, the author deploys a simplified fuel consumption model and conduct case study analyses to compare different routes environmentally and economically. Findings – The results explain why at times of low fuel prices as in 2020, canals provided discounts to entice ship operators to keep transiting these, instead of opting for longer routes. Considering the ongoing repercussions of the pandemic in supply chains, as well as the potential introduction of market-based measures in shipping, the value of transiting canals will be much higher in the coming years. Research limitations/implications – The main limitation in this work is that the author used the publicly available information on canal tolls, for the different ship types examined. Practical implications – The envisioned model is simple, and it can be readily used for any ship and route (port to port) combination available, if ship data are available to researchers. Social implications – It is possible that canal tolls will increase, to account for the additional environmental benefits brought to ship operators. Originality/value – The methodology is simple and transferable, and the author proposes several interesting research questions for follow-up work.
Keywords: Route choice; Shipping decarbonization; Disruptions; Maritime transport; Shipping canals